Andrographolide Alleviates Acute Brain Injury in a Rat Model of Traumatic Brain Injury: Possible Involvement of Inflammatory Signaling - Tao, Li; Zhang, Li; Gao, Rong; Jiang, Feng; Cao, Jianbo; Liu, Huixiang (Frontiers in Neuroscience, 2018)
Neuroinflammation plays an important role in secondary injury after traumatic brain injury (TBI). Andrographolide (Andro), a diterpenoid lactone isolated from Andrographis paniculata, has been demonstrated to exhibit anti-inflammatory activity in neurodegenerative disorders. This study therefore aimed to investigate the potential neuroprotective effects of Andro after TBI and explore the underlying mechanisms. In our study, we used a weight-dropped model to induce TBI in Sprague–Dawley rats, the neurological deficits were assessed using modified neurological severity scores, Fluoro-Jade B (FJB) and terminal deoxynucleotidyl transferase (TdT) dUTP Nick-End Labeling (TUNEL) staining were employed to examine neuronal degeneration and apoptosis after TBI, immunofluorescence was designed to investigate microglial activation. Quantitative Real-time PCR and ELISA were conducted to detect the expression levels of pro-inflammatory cytokines, Western blot was used to examine the expression level of proteins of relative signaling pathway. Our results showed that after Andro administration, the neurological deficit was attenuated, and the cerebral edema and apoptosis in brain tissues were also decreased following TBI. Both microglial activation and the expression of pro-inflammatory cytokines were significantly inhibited by Andro after TBI. Moreover, Andro inhibited NF-κB p65 subunit translocation and decreased the expression levels of phosphorylated extracellular signal regulated kinase (ERK) and p38 MAPK after TBI. Altogether, this study suggests that Andro could improve neurobehavioral function by inhibiting NF-κB and MAPK signaling pathway in TBI, which might provide a new approach for treating brain injury.